Exogenous Glutathione Enhances Mercury Tolerance by Inhibiting Mercury Entry into Plant Cells - Kim, Yeon-Ok; Bae, Hyeun-Jong; Cho, Eunjin; Kang, Hunseung (Frontiers in Plant Science, 2017)
Despite the increasing understanding of the crucial roles of glutathione (GSH) in cellular defense against heavy metal stress as well as oxidative stress, little is known about the functional role of exogenous GSH in mercury (Hg) tolerance in plants. Here, we provide compelling evidence that GSH contributes to Hg tolerance in diverse plants. Exogenous GSH did not mitigate the toxicity of cadmium (Cd), copper (Cu), or zinc (Zn), whereas application of exogenous GSH significantly promoted Hg tolerance during seed germination and seedling growth of Arabidopsis thaliana, tobacco, and pepper. By contrast, addition of buthionine sulfoximine, an inhibitor of GSH biosynthesis, severely retarded seed germination and seedling growth of the plants in the presence of Hg. The effect of exogenous GSH on Hg specific tolerance was also evident in the presence of other heavy metals, such as Cd, Cu, and Zn, together with Hg. GSH treatment significantly decreased H2O2 and O2- levels and lipid peroxidation, but increased chlorophyll content in the presence of Hg. Importantly, GSH treatment resulted in significantly less accumulation of Hg in Arabidopsis plants, and thin layer chromatography and nuclear magnetic resonance analysis revealed that GSH had much stronger binding affinity to Hg than to Cd, Cu, or Zn, suggesting that tight binding of GSH to Hg impedes Hg uptake, leading to low Hg accumulation in plant cells. Collectively, the present findings reveal that GSH is a potent molecule capable of conferring Hg tolerance by inhibiting Hg accumulation in plants.